The Impact of Transformational Leadership on Citizen Satisfaction with Public Service Delivery - Nida Silvia Lestari; Nindi Riyan Gustin; Tifani Adnisa Geni (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the impact of transformational leadership on citizen satisfaction with public service delivery in Indonesian local government context through a cross-sectional survey of 384 citizens in Tanah Datar Regency, West Sumatra, selected via stratified random sampling. Data were collected using validated instruments measuring transformational leadership (MLQ) and citizen satisfaction (adapted SERVQUAL), then analyzed using Structural Equation Modeling (SEM). Findings reveal that transformational leadership significantly predicts citizen satisfaction with public service delivery (β = 0.672, p < 0.001), with inspirational motivation (β = 0.284, p < 0.001) and individual consideration (β = 0.267, p < 0.001) showing the strongest effects. The model explains 45.2% of variance in citizen satisfaction, with service responsiveness and reliability emerging as key mediating factors. Results demonstrate that transformational leadership practices significantly enhance citizen satisfaction with public service delivery in local government settings, where leaders demonstrating inspirational motivation and individual consideration achieve higher citizen satisfaction levels. Practical implications suggest that local governments should prioritize transformational leadership training for public officials, emphasizing inspirational communication and personalized attention to citizen needs to improve public service delivery effectiveness, thereby contributing to the growing literature on public leadership effectiveness in developing country contexts.